The Constitutional Dilemmas on Cases of Incompatibility and Conflict of Interest of Members of Parlament in Albania - Fjorida Ballauri (European Scientific Journal, ESJ, 2026)
This paper examines the constitutional and legal framework governing the incompatibilities of the mandate of a Member of Parliament in the Republic of Albania, with particular emphasis on the prevention of conflicts of interest and the protection of the integrity of public office. The analysis focuses on Article 70 of the Constitution, which prohibits deputies from exercising other state functions or engaging in activities that derive benefits from public property, alongside the law on the prevention of conflicts of interest, which establishes additional restrictions applicable to deputies and persons related to them.The central research question is whether incompatibility cases provided by statutory law constitute valid legal grounds for the termination of a parliamentary mandate. To address this issue, the study examines the relevant jurisprudence of the Constitutional Court, the various limitations on the private interests of deputies and related persons, as well as the respective roles of the Assembly of Albania and the High Inspectorate for the Declaration and Audit of Assets and Conflict of Interest. The findings indicate that, despite the existence of an extensive normative framework, inconsistencies in practical application and ambiguities in the allocation of powers between the Assembly and the Constitutional Court have undermined the establishment of a coherent and unified standard for parliamentary incompatibility.The paper concludes by emphasizing the need for clearer legal regulation of incompatibility cases, enhanced inter-institutional coordination, and strengthened control mechanisms to ensure effective implementation of the principles of parliamentary integrity and accountability in Albania.